2016
DOI: 10.1136/bmjopen-2016-012021
|View full text |Cite
|
Sign up to set email alerts
|

Choice of Moisturiser for Eczema Treatment (COMET): feasibility study of a randomised controlled parallel group trial in children recruited from primary care

Abstract: ObjectivesTo determine the feasibility of a randomised controlled trial of ‘leave on’ emollients for children with eczema.DesignSingle-centre, pragmatic, 4-arm, observer-blinded, parallel, randomised feasibility trial.SettingGeneral practices in the UK.ParticipantsChildren with eczema aged 1 month to <5 years.Outcome measuresPrimary outcome—proportion of parents who reported use of the allocated study emollient every day for the duration of follow-up (12 weeks). Other feasibility outcomes—participant recruitme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
30
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 21 publications
(31 citation statements)
references
References 17 publications
0
30
0
1
Order By: Relevance
“…There is no standard definition of infected eczema, so we used pragmatic inclusion criteria based on clinical suspicion of infection. Included children were clearly experiencing flares in their eczema, considering that their mean baseline POEM scores were higher than those found in other ambulatory care studies (8.9 and 9.8 in COMET 23 and BATHE 24 studies respectively; unpublished data), there was a significant improvement in severity scores during the follow-up period in all groups, more than 90% had 1 or more "classical" signs of infection, and 70% had S. aureus isolated from baseline swabs. Fewer than one-third, however, had moderate to severe crusting, and only 1 in 10 had moderate to severe weeping, so it is possible that not all participants had actual infection.…”
Section: Strengths and Limitationsmentioning
confidence: 51%
“…There is no standard definition of infected eczema, so we used pragmatic inclusion criteria based on clinical suspicion of infection. Included children were clearly experiencing flares in their eczema, considering that their mean baseline POEM scores were higher than those found in other ambulatory care studies (8.9 and 9.8 in COMET 23 and BATHE 24 studies respectively; unpublished data), there was a significant improvement in severity scores during the follow-up period in all groups, more than 90% had 1 or more "classical" signs of infection, and 70% had S. aureus isolated from baseline swabs. Fewer than one-third, however, had moderate to severe crusting, and only 1 in 10 had moderate to severe weeping, so it is possible that not all participants had actual infection.…”
Section: Strengths and Limitationsmentioning
confidence: 51%
“…Different methods are available to measure the water content of the outer layers of epidermis, and there are few studies comparing these approaches with the patient‐reported or clinical assessments in our study. Corneometry readings were collected in participants’ homes with variable temperature and humidity, which we measured and adjusted for in our analyses . However, the observed variability in readings may reflect other factors, such as time since bathing or application of emollient.…”
Section: Discussionmentioning
confidence: 99%
“…The corneometer was chosen over the measurement of TEWL primarily because of the portability and robustness of the instrument. While standardized procedures written in accordance with guidelines on biophysical skin measurements were followed, measurements were taken in participants’ homes under uncontrolled conditions. Skin hydration was analysed in a multivariate linear regression model adjusted for variations in room temperature and humidity .…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…also evaluated an educational support programme, which included the provision of an educational DVD and telephone support . Moisturizers or barrier creams were evaluated in six studies . Other preparations evaluated included fluticasone propionate ointment; topical prednicarbate; and some oral preparations, including montelukast, bacterial lysate, ciclosporin A and antibiotics (vs. an antibiotic cream) for infected eczema .…”
Section: Resultsmentioning
confidence: 99%